Marriage to the Same Kind: Organizational Political Ideology and Mergers and Acquisitions - Chow, Dawn Yi Lin; Louca, Christodoulos; Petrou, Andreas; Procopiou, Andreas (My University, 2021)
This study contributes to the growing literature on organizational political ideology by positing that acquiring firms choose targets with similar organizational political ideology in their effort to retain employees post-merger. Using a sample of M&A announcements in the United States from 1996 to 2014, we find a positive relationship between the similarity of political ideologies of the merging organizations and the likelihood of M&A announcement. In addition, we find that our main relationship is stronger the more homogeneous the organizational political ideology of the acquirer, and the more the human capital intensity of the merging firms. In addition, we find support for the proposed mechanism that drives the main relationship. We thus introduce the concept of organizational political ideology into the debate over the influence of organizational values in M&As, and we extend the theoretical application of political ideology to settings with inter-organizational partnerships.
Keywords: Employee retention; Identity; Mergers and acquisitions; Panel and pooled analysis; Political ideology